THEORETICAL MODELS OF TOXICOMANIA PREVENTION:A PROPOSAL OF TAXONOMY - Carlos Pastor, Juan; López-Latorre, Mª Jesús (Anales de Psicología / Annals of Psychology)
The purpose of this paper is to describe and examine the major models in use proposed in the field of alcohol and drug abuse, from their prevention implications. Our proposal of classification include the disease model, the legal model, the distribution of consumption model, the sociological model, the sociocultural model, the psychosocial model and the ecological model. Each of them is described in terms of the assumptions they make about substance abuse and individual substance abuser, and about the etiology and factors emphasized as critical elements to adress interventions. The major prevention strategies suggested from each of these models are also examined.